Transformational Leadership Practices and Institutional Decision-Making Among Graduate School Professors and College Officials: The Northeastern College Lens - Pascual, Sabina; Pascual, Sabina (International Journal of Arts, Sciences and Education, 2026)
Transformational leadership has become increasingly significant in higher education institutions as academic leaders face complex organizational demands, institutional reforms, and quality assurance requirements. This study explored the transformational leadership practices and institutional decision-making experiences among graduate school professors and college officials in Northeastern College, Santiago City. Using a qualitative phenomenological research design, the study gathered data from purposively selected graduate school professors, academic coordinators, deans, and college officials through semi-structured interviews. Data were analyzed using Braun and Clarke’s thematic analysis framework. Findings revealed that transformational leadership practices were manifested through collaborative governance, inspirational academic leadership, faculty empowerment, and participatory institutional planning. Participants emphasized that inclusive decision-making processes strengthened organizational trust, faculty engagement, and institutional effectiveness. However, challenges such as communication gaps, workload pressures, and resource limitations affected institutional decision-making processes. The findings underscore the importance of transformational leadership in promoting organizational adaptability, shared governance, and academic excellence in higher education institutions. The study contributes to educational leadership literature by highlighting the role of participatory leadership practices in sustaining institutional development in private higher education institutions in the Philippines.